Go figure : energies, forms, and institutions in the early modern world - Anderson, Judith H.; Linton, Joan Pong (Fordham University Press, 2011)
This title addresses theories of the figure and practices of figuration ranging from classical rhetoric and biblical exegesis to semiotics, psychoanalysis, and socio-politics.